2018
DOI: 10.5325/jdevepers.2.1-2.0062
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality and Resource Sharing: Evidence from Rural Nicaragua

Abstract: Gender inequality in access to resources remains persistent in rural areas in developing countries. To better understand the mechanisms responsible for gender inequality, we start from the observation that access to resources in rural villages is largely determined by within-village resource sharing, which is embedded in social networks. It is therefore important to study the influence of gender on resource sharing while taking account of the social networks of men and women. To do so, we combine data from a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Food and provision of food produced and reproduced power inequalities [10], social status, competition, and agency. There was a strong normative assumption about men's need to provide food in general, and specifically to their male friends and their girlfriends, which established identity and power hierarchies in these contexts [9,10,[38][39][40][41]. Food sharing wasn't simply a prosocial act, as sharing food and drink seemed to garner status amongst men, and YPRA accounts revealed that who was witnessing this sharing was also important in shaping social status [38,42].…”
Section: Discussionmentioning
confidence: 99%
“…Food and provision of food produced and reproduced power inequalities [10], social status, competition, and agency. There was a strong normative assumption about men's need to provide food in general, and specifically to their male friends and their girlfriends, which established identity and power hierarchies in these contexts [9,10,[38][39][40][41]. Food sharing wasn't simply a prosocial act, as sharing food and drink seemed to garner status amongst men, and YPRA accounts revealed that who was witnessing this sharing was also important in shaping social status [38,42].…”
Section: Discussionmentioning
confidence: 99%